The Juridical Analysis Of Conventional Or Electronic Procurement Of Goods And Services And The Role Of Government Supervisory Agency - Yardie David Roringkon; Yayan Hanapi; Leni Nurmala; Yusrianto Kadir; Ibrahim Ahmad (IHSA Institute, 2022)
Procurement of goods and services through electronics (e-procurement) is a system that can be applied because it is more transparent, effective and efficient when compared to the conventional system of procurement of goods and services (face to face). In this article the author limits the study of the effectiveness of the application of law to the procurement of goods/services by the government which is carried out through conventional and electronic methods. In this paper, using a normative juridical method, namely analyzing the enactment of the rule of law and then describing it systematically. The current legislation regarding the procurement of goods and services through electronics can be said to be ineffective because the legal regulations have not specifically regulated this matter, both in substance and in technical implementation. So it is necessary to immediately establish a law that regulates the procurement of goods and services through electronics (e-Procurement). This regulation will be the basis for implementing e-Procurement, given the increasingly complex problems in the procurement of goods and services, these regulations continue to be adjusted and changes and improvements are made, both in terms of substance and technical supporting regulations.